(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The most common failures and reasons for subsequent repair of large-scale sliding bear-ings are: deviation from the initial geometric shape of the friction surfaces, scratches and cuts occurring on the friction surfaces, tolerances and defects as a result of diameter and length discrepancies – sagging, bending, divergence, axles intersection and boundary wear. Sliding bearings and the bearing journals below them are flaw detected by measuring the bearing sur-face macrogeometry, followed by a comparison with the standard tolerances and defects at var-ious diameters and lengths, and inspection of the defects. The present study analyses different friction surfaces of large-scale sliding bearings and the results show a correlation between the type of wearing, the relative position of the bearing supports and the deviations from the correct geometric shape of the friction surfaces. A qualitative correlation between the type of wearing and the relative position of the two bearing supports has been investigated and established. Bearing journal wear is out of the scope of the present study.